CONFLICT BETWEEN SOCIETIES AND COMPANIES IN THE CONTEXT OF OWNERSHIP - Agustiyara (IPEM 16 UMY 257, 2016)
The research aims to describe the agrarian conflict in Central Borneo and to analyse the agrarian conflict resolution practices in an appropriate way. Agrarian conflict in Central Borneo caused by various factors, First, inequality spatial planning of forestry and overlapping of ownership. Second, the expansion of oil palm plantation is increasing every year, and the government ambition to make oil palm plantation as the main commodity in Central Borneo. Every year there are so many conflicts, but in this research divided into four types, the conflict between community and company, community and community, company and state, and community and state. Conflict over the land and natural resource often occur where there is overlapping resource interest among groups, communities, and state. Therefore, the hypothesis is discussed by reference to find the sustainability way of oil palm plantation regarding the environment, social, and culture aspect. Second, the expansion of oil palm plantation without damaging forest zone, and third, the strengthen of spatial planning of forestry, operational regulation to support and protect land ownership. Keywords: Agrarian Conflict, Land Tenure, Resolution Practices